Implementing the Trade Facilitation Agreement should boost trade among African Continental Free Trade Area members - Jaime De Melo; Zakaria Sorgho; Laurent Wagner (Fondation pour les études et recherches sur le développement international (FERDI), 2024)
The main objective of the African Continental Free Trade Area is to eliminate trade barriers and boost intra-Africa trade. This column argues that implementing the Trade Facilitation Agreement's provisions would be a powerful complement to the free trade area's tariff-reduction agenda. A realistic implementation of TFA measures could reduce time in customs for imports by 2.7 days for exports by 1.7 days. These reductions in time translate into a tariff ad-valorem equivalent reduction in the range 3.6-7% for imports and an 8.1% extra growth for exports.
Keywords: 330; Africa; Preferential trade agreements (PTAs); AfCFTA